Meet Peter Rabbit's friends - Potter, Beatrix, 1866-1943. (New York : Frederick Warne, 2005)
An illustrated introduction to Peter Rabbit's friends.
Cover title.
On Board pages.
Keywords: Characters in literature -- Juvenile fiction; Friendship -- Juvenile fiction; Peter Rabbit (Fictitious character) -- Juvenile fiction; Rabbits -- Juvenile fiction; Characters in literature -- Fiction; Friendship -- Fiction; Peter Rabbit (Fictitious character) -- Fiction; Rabbits -- Fiction